2005
DOI: 10.1002/prot.20837
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific transamidation and deamidation of the small heat‐shock protein Hsp20 by tissue transglutaminase

Abstract: Crosslinking of small heat-shock proteins (sHsps) by tissue transglutaminase (tTG) is enhanced by stress and under pathological conditions. We here used hexapeptide probes to determine the amine donor (K) and acceptor (Q) sites for tTG in Hsp20. Mass spectrometric peptide mass fingerprinting and peptide fragmentation established that Q31 and the C-terminal K162 are involved in inter- and intramolecular crosslinking (transamidation). Q31 is a conserved glutamine in sHsps where the neighboring residue determines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…However, because the higher molecular mass forms detected here are present after denaturing electrophoresis, they must be formed by covalent cross-linking of multiple monomers to themselves (the molecular mass of the major forms in mouse suggests a trimer) or other proteins. In amyloid plaques, HspB1 is cross-linked into large multi-species protein aggregates by tissue transglutaminase (37). HspB1 has multiple glutamine and lysine residues, making it a potential substrate for the abundant transglutaminases in the upper epidermis that become active developmentally when HspB1 monomer is lost.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the higher molecular mass forms detected here are present after denaturing electrophoresis, they must be formed by covalent cross-linking of multiple monomers to themselves (the molecular mass of the major forms in mouse suggests a trimer) or other proteins. In amyloid plaques, HspB1 is cross-linked into large multi-species protein aggregates by tissue transglutaminase (37). HspB1 has multiple glutamine and lysine residues, making it a potential substrate for the abundant transglutaminases in the upper epidermis that become active developmentally when HspB1 monomer is lost.…”
Section: Discussionmentioning
confidence: 99%
“…At best, deamination reactions were believed to be favored only under certain conditions such as lower than physiological pH [27]. It was rarely, if at all, considered that TG2 might actually deaminate a protein even when conditions were permissive for transamidation until a study showed that a glutamine residue in Hsp20 was specifically deaminated while other glutamine residues were transamidated [28]. Further studies showed that specific deamination is observed in other proteins as well [29], and the number of reports examining the structural features of substrates that favor deamination over transamidation is growing [29, 30].…”
Section: Tg2: Transamidating/deaminating Functionmentioning
confidence: 99%
“…The deamidation reaction, which is favored with poor substrates, low TG concentrations, and low pH (Stamnaes et al, 2008), has a certain degree of substrate specificity. For example, TG2 caused deamidation of Gln66 and transamidation of Gln31 to Lys162 in Hsp20 protein (Boros et al, 2006). The deamidating function of TG2 received much attention when it was reported to catalyze deamidation of peptides derived from the wheat protein gliadin, causing them to become dominant epitopes for activating T cells associated with the pathogenesis of celiac disease (Shan et al, 2002; Sollid and Jabri, 2005).…”
Section: Enzymatic and Nonenzymatic Activities Of Tg2mentioning
confidence: 99%